Resolving Jurisdictional Disputes Between the Central Executive Board of Political Parties and DPRD Factions in Regional Policymaking: A Constitutional Law and Democratic Governance Perspective - Muhsin Yusuf; Taufik Firmanto; Erham Erham (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the relationship between the Central Executive Board (Dewan Pimpinan Pusat—DPP) of political parties and regional legislative factions (Fraksi DPRD) should be structured proportionally based on the principles of the rule of law, popular sovereignty, and constitutional democracy, thereby ensuring that party discipline operates in harmony with the institutional independence of legislative factions in exercising their legislative, budgeting, and oversight functions. In practice, however, the boundaries of authority between these institutions remain ambiguous, resulting in recurring jurisdictional disputes over regional policymaking that have not been comprehensively regulated under Indonesian positive law. This study aims to examine the constitutional and legal position of the DPP and DPRD factions, analyze the dynamics of jurisdictional disputes between them, and formulate an appropriate dispute resolution model from the perspective of constitutional democracy. This research employs normative legal research with a qualitative approach using the statute, conceptual, and case approaches. Data were analyzed prescriptively through statutory interpretation, legal doctrines, and relevant scholarly literature. The findings reveal that jurisdictional disputes primarily arise from the overlap between the organizational authority of political parties and the public authority vested in DPRD factions. The proposed model emphasizes a coordinative institutional relationship, normative limitations on DPP intervention, strengthened internal party dispute resolution mechanisms, regulatory reform, and judicial safeguards to balance party discipline, factional independence, and the constitutional mandate of the people.